Comparação entre métodos de medição da camada semi-redutora em radiologia (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The Half Value Layer (HVL) is a parameter used in Quality Control (QC), to evaluate the X-ray beam quality. The HVL can be measured through the X-ray primary beam attenuation measurement using knew thickness slabs of 99% purity aluminum (M1) or by adjusting the best curve (M2) or by multipurpose dosimeter (solid state detector) (M3). The M1 wears out the X-ray tube more and requires a long time of data acquisition and processing, however, it is the standard recommended method for the Radiological Safety Manual. The last one method (M3) is practical, and is not influenced by the abrupt change in the X-ray transmission spectrum, as it does not require the use of aluminum plates. The equipment used to measure radiation was the NOMEX dosemeter, Cobia Smart, UNFORS XI and Radcal Ionization Chamber. The sources were mobile and fixed X-rays and mammography equipment. The results showed that the biggest difference was 15.6% between M1 and M3 for mammography equipment with a filter\target W\Rh. For conventional X-rays, that the target-filter combination is W\Al, the biggest difference was 3.3% between M1 and M3. Thus, the results show that the HVL estimate can be performed by any of the three methods or equipment, as long as the target\filter combination is W/Al. For filter\target combination other than W/Al the percentage differences increase considerably and we do not recommend the use of M1 for this type of measurement.